Patton's pawns : the 94th US Infantry Division at the Siegfried Line - Le Tissier, Tony, 1932- (University of Alabama Press, 2007)
The 94th US Infantry Division was an organization formed late in the Second World War, made up of draft-deferred university students as enlisted men and an officer corps pulled together from various domestic postings. This book presents a study of the fighting between the 94th US Infantry Division and their German counterparts.